Number of rare germline CNVs and TP53 mutation types - Silva, Amanda G (BioMed Central, 2012)
BACKGROUND: The Li-Fraumeni syndrome (LFS), an inherited rare cancer predisposition syndrome characterized by a variety of early-onset tumors, is caused by different highly penetrant germline mutations in the TP53 gene; each separate mutation has dissimilar functional and phenotypic effects, which partially clarifies the reported heterogeneity between LFS families. Increases in copy number variation (CNV) have been reported in TP53 mutated individuals, and are also postulated to contribute to LFS phenotypic variability. The Brazilian p.R337H TP53 mutation has particular functional and regulatory properties that differ from most other common LFS TP53 mutations, by conferring a strikingly milder phenotype. METHODS: We compared the CNV profiles of controls, and LFS individuals carrying either p.R337H or DNA binding domain (DBD) TP53 mutations by high resolution array-CGH. RESULTS: Although we did not find any significant difference in the frequency of CNVs between LFS patients and controls, our data indicated an increased proportion of rare CNVs per genome in patients carrying DBD mutations compared to both controls (p=0.0002***) and p.R337H (0.0156*) mutants. CONCLUSIONS: The larger accumulation of rare CNVs in DBD mutants may contribute to the reported anticipation and severity of the syndrome; likewise the fact that p.R337H individuals do not present the same magnitude of rare CNV accumulation may also explain the maintenance of this mutation at relatively high frequency in some populations.